A recent progress of graphene oxide/metal oxide composite for humidity sensor applications / Fazlinashatul Suhaidah Zahid ... [et al.] - Zahid, Fazlinashatul Suhaidah; Md Sin, Nor Diyana; Muhamad Ngadi, Nur Amalina; Hussin, Mohamad Zhafran (Faculty of Applied Sciences, 2023)
In this article, we have reviewed current research findings on a unique material known as graphene oxide (GO), which is a by-product of the oxidation of graphene, to assess its use as potential carbon material in metal oxide composites-based humidity sensors. Due to its exceptional mechanical, electrical, and optical properties, graphene oxide (GO) has garnered significant interest in numerous scientific and technological domains. A GO/metal oxide-based humidity sensor deposition has been made using various nanoparticles that offer an excellent interface and low defect levels in the heterostructure. This paper summarises recent developments in GO and GO/metal oxide composites for sensing materials. We begin with the principles of humidity sensing, the synthesis of graphene materials, and the deposition method of GO and GO/metal oxide composites. Moreover, the characterization, such as structural, morphology, optical, and electrical properties, was discussed based on X-ray diffraction measurement (XRD), Field emission scanning electron microscopy (FESEM), photoluminescence (PL), and current voltage (IV characteristics). This review also highlights sensor properties such as sensitivity, selectivity, stability, response time, and detection limits. Most of the findings also revealed that the highly effective sensing mechanism was used to detect respective characterizations with high sensitivity and stability. The present review is focused on exploring the synthesis, deposition, and characterization of GO and GO/metal oxide composite-based humidity sensors.